PEMBERDAYAAN KADER ‘AISYIYAH DALAM TANGGAP BENCANA SEBAGAI UPAYA MENGURANGI DAMPAK BENCANA - Roza Aryani; Afriana Afriana; Evi Kurniawati (Jurnal Abdimas Bina Bangsa, 2023)
This relates to the geographical location of Indonesia which is located between the two major oceans and is located in the area of ​​tectonic plates. Indonesia's location is located on a tectonic plate or is also included in the ring of fire, which means that Indonesia is prone to earthquakes and can cause tsunamis. Health services during a disaster are one of the most important factors to prevent death, disability, and illness. There are three topics in this disaster training, namely, first, pregnant women with hypertension who were brought to the health service post but could not be handled at the post, and then referred, second, accident patients with head injuries and died on the spot, and third, accident patients with broken legs and taken to the post. health services. This training is carried out by counseling and simulation methods directly to cadres. In this activity the participants played an active role, this was aimed at increasing the knowledge and skills of the 'Aisyiyah cadres in disaster response after the evaluation was completed. The result of this activity is that Aisyiyah cadres understand how to deal with patients who urgently need help and work together with health workers